Connecting Hospitalized Patients with Their Families: Case Series and Commentary - Kourosh Parsapour; Alexander A. Kon; Madan Dharmar; Amy K. McCarthy; Hsuan-Hui Yang; Anthony C. Smith; Janice Carpenter; Candace K. Sadorra; Aron D. Farbstein; Nayla M. Hojman; Gary L. Wold; James P. Marcin (International Journal of Telemedicine and Applications)
The overall aim of this project was to ascertain the utilization of a custom-designed telemedicine service for patients to maintain close contact (via videoconference) with family and friends during hospitalization. We conducted a retrospective chart review of hospitalized patients (primarily children) with extended hospital length of stays. Telecommunication equipment was used to provide videoconference links from the patient's bedside to friends and family in the community. Thirty-six cases were managed during a five-year period (2006 to 2010). The most common reasons for using Family-Link were related to the logistical challenges of traveling to and from the hospital—principally due to distance, time, family commitments, and/or personal cost. We conclude that videoconferencing provides a solution to some barriers that may limit family presence and participation in care for hospitalized patients, and as a patient-centered innovation is likely to enhance patient and family satisfaction.